The Effect of Game-Based Training Approach on The Understanding of Tactical Skills in Adult Tennis Players - Tristan Suryaji; Yadi Sunaryadi; Yudi Nurcahya (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
The purpose of this study was to determine the effect of game-based training on the tactical skills understanding of adult tennis players at Sigma Tennis Club Bandung.. The method used in this study was an experiment using a One Group Pretest-Posttest Design. The population in this study were 10 tennis players training at Sigma Tenis Club Bandung, while the sample size was 10 people. The sampling technique used was total sampling, where all members of the population were used as samples in the study. The research instrument used a questionnaire referring to the Tactical Skills Questionnaire Test. Based on data processing and analysis, the average tactical skills performance test score increased from 63.00 to 84.30. The results of the paired sample t-test on both variables showed a sig. (2-tailed) of 0.000 < 0.05. Thus, Ho was rejected and Ha was accepted. Therefore, it can be concluded that Game-Based Approach training significantly improves the tactical skills of adult tennis players.